Early menarche is associated with non‐alcoholic fatty liver disease in adulthood. Issue 12 (20th December 2017) - Yi, Kyung Hee; Hwang, Jin Soon; Lim, Se Won; Lee, Jun Ah; Kim, Dong Ho; Lim, Jung Sub
Abstract: Background: The aim of this study was to examine the association between early menarche (<12 years) and non‐alcoholic fatty liver disease (NAFLD) in premenopausal women and to explore whether it is mediated by adult obesity and insulin resistance. Methods: We analyzed data of premenopausal women, aged ≥15 years, from the Korea National Health and Nutrition Examination Survey (2007–2009). We divided the women into three groups: early menarche, reference (12.00–15.99 years), and late menarche. The presence of NAFLD was determined using hepatic steatosis index >36.0. Results: Of the 4, 387 women evaluated, 673 (15.4%) met the criteria for NAFLD. The prevalence of NAFLD was higher in both women with early and late menarche compared with the reference (early, 23.4%; reference, 14.0%; late, 19.9%, P < 0.001). After adjustment of confounders including age, the OR for NAFLD in early menarche compared with the reference was 3.04 (95%CI: 1.99–4.65). Further adjustment of mediators, such as central obesity or insulin resistance, attenuated the association to 1.91–2.17. There was no association, however, between late menarche and NAFLD after adjustment of confounders. Conclusions: Early menarche was associated with an increased risk of NAFLD in young and middle‐aged premenopausal Korean women.